Distribution of DNA damage in chromatin and its relation to repair in human cells treated with 7-bromomethylbenz(a) anthracene. - Oleson, F B (1979)
We have examined the relationship between the distribution of DNA damage and repair in chromatin from confluent human fibroblasts treated with the carcinogen 7-bromomethylbenz (a) anthracene. Analysis of staphylococcal nuclease (SN)4 digestion kinetics and gel electrophoresis revealed that more total damage occurs in nucleosome core DNA (approximately 80-85% of chromatin DNA) than in SN sensitive DNA (APPROXIMATELY15-20%). Furthermore, over a 24 hr period, damage is removed at about the same rate from these two regions. In contrast, virtually all of the nucleotides incorporated during repair synthesis are initially SN sensitive even when measured at 12 hr after damage. With time many repair-incorporated nucleotides become SN resistant and coelectrophorese with nucleosome core DNA. To explain these data we propose a model whereby excision repair occurs in both linker and core DNA; however, in core DNA the repair process induces conformational changes resulting in temporarily increased SN sensitivity; subsequently, rearrangement occurs and results in the re-establishment of native or near-native nucleosome conformation and SN resistance.